Migration and mimetism (Religious dialogue and cooperation, 2020)
The purpose of this study is not to examine the legalaspects of migration or to cover the field of security policy, butthe general theoretical examination of the topic of migrationregarding the issue of the origin of conflicts, as well as of the topicof violence and religion. Concerning the realm of religious study, Iintend to argue in favor of a viewpoint that religious difference, as acivilization or culture line or gap, does not constitute in itself a directcause of violence. Regarding international migration, I claim thatthe origin of the conflicts is much more rooted in global rivalry thanin religious or other cultural differences. In my view, the classicaltheories of migration fail to grasp the essential cause of conflicts.This is because these concepts generally explain migration by purelyeconomic factors regardless of human desire and violence. In myopinion, René Girard’s concept of mimetic desire might be a usefulapproach to analyze the issue of migration, because it focuses onthe human factor and Girard enlights the systematic relationshipbetween violence and desire. Based on Girard’s concept of mimesis,I attempt to outline a particular and plausible framework ofinterpretation regarding the relationship between the motivationalbackground of migration and the development of conflicts. As aresult of this study, I can claim that the mimetic theory can providea significant additive and perspective to the research on migration,both in terms of possible aspects of data collection and in terms ofsecondary analysis of data or interpretation.
Keywords: violence and religion; migration; mimetism; mimetic theory; René Girard